Succession Planning in Family Business: A Case Study of PT BBL - M. Hamdani Pratama; J.E Sutanto (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the succession planning process in a family business at PT BBL, a company that produces raw materials for animal feed based in Sidoarjo. The transition of leadership from the founding generation to the next generation is a strategic issue that determines the sustainability of the company. Using a qualitative approach with case studies, data were obtained through in-depth interviews with the founder’s generation, the second generation, corporate professionals, and family business experts. This study adapts the Seven-Pointed Star model (Rothwell, 2010), which was developed into eight stages, to describe the dynamics of succession that are relevant to the context of SUCCESSION PLANNING IN FAMILY BUSINESS: A CASE STUDY OF PT BBL. The results of the study show that PT BBL is still in the early stages of succession planning, with the main challenges including the development of affective commitments, the harmonization of values and expectations between generations, and the improvement of the competency readiness of the next generation. These findings provide theoretical contributions by enriching the study of family business succession in Indonesia, as well as practical implications for designing a succession strategy that is structured, sustainable, and aligned with family values.